A 'novel' approach to leadership development : using women's literary fiction to explore contemporary women's leadership issues : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Business Studies in Management at Massey University, Albany, New Zealand - Martin, Lydia Anne (Massey University, 2016)
The central aim of this thesis is to investigate how women’s literary fiction can be harnessed for the purpose of exploring contemporary women’s leadership issues. This thesis argues that literary fiction is a valuable source of interdisciplinary and ‘artful’ consciousness-raising material for proactively addressing at the interpersonal level a wide range of critical concerns related to women’s leadership experiences. Having identified a significant ‘gap’ in the extant literature – the underutilisation of women’s novels, short-stories and plays in leadership studies – this thesis adopts an interdisciplinary approach to demonstrate how literary works can be used to examine women’s contemporary leadership issues. For this research project I adopted an interpretive qualitative research paradigm informed by critical leadership studies and a multiplicity of feminist perspectives. I developed a systematic method for long listing and short listing appropriate texts and analysed selected works in response to a five-point conceptual framework of critical concerns arising from a review of the women and leadership literature. I also kept a reflective blog to track the iterative nature of the research process and to record my learning during this study. The findings demonstrate that women’s literary fiction offers a rich repository of thought-provoking illustrations of women’s leadership concerns, including gender binaries, power-play, socially constructed perceptions and gendered expectations, and women’s diverse range experiences as both leaders and followers. The extended analysis provides a number of in-depth examples and reflective questions, revealing myriad opportunities for critical theorising, illustrative analysis and critical reflection. Subsequently, this thesis argues that fictional stories are a viable and potentially transformative ‘artful’ intervention for addressing complex leadership issues concerned with gender within the context of women’s leadership development programmes. My recommendations for future studies include a focus on ethical leadership, the evaluation of participant ‘book club’ interventions and an extension of the reading lists to include more culturally relevant New Zealand authors. To my knowledge, there are no studies that utilise women’s literary fiction for the purpose of exploring contemporary women’s leadership concerns and questions. Consequently, my thesis makes an original contribution to the leadership and humanities field, as well as providing an innovative and creative product that can be used for critical and interdisciplinary approaches to women’s leadership development.
Keywords: Leadership in women; Fiction; Women authors; Women in literature; Leadership in literature